Respon Pertumbuhan Tunas Mahkota Nanas (Ananas comosus (L.) Merr) dengan Penambahan Benzyl Amino Purine (BAP) dan Naphthalene Acetic Acid (NAA) - Riza Linda, Feryati, Mukarlina (Universitas Tanjungpura, 2018)
Pineapple (Ananas comosus (L.) Merr) is a vital horticulture product for its economic value and high nutritional value. One of the alternatives to reproduce pineapple is by a means of in vitro. It aims to produce a similar seed as its parent. Then, it can cater seed’s necessity for a large scale in a short time. This research aims at identifying the response of the addition of BAP and NAA towards the growth of the shoot crown of the pineapple and to figure out the best concentration of BAP and NAA for the shoot crown’s growth. The research was conducted for 5 months since February to July 2017 at tissue culture laboratory of Aloe Vera Centre Pontianak. The research applied a Completely Randomised Design (RAL) with a factorial pattern as the following factors. The first factor was BAP (B) with the concentrations of 0 M (B0), 10-7 M (B1), 10-6 M ( B2), 5×10-6 M (B3) and the second factor was NAA (N) 0 M (N0), 10-7 M (N1), 5×10-6 M (B2). Results show that the best concentration was 10-7 M BAP + 0 M NAA with the average rates of crown and leaves were 2 and 8.66 respevtively.